2020
DOI: 10.1111/1348-0421.12838
|View full text |Cite
|
Sign up to set email alerts
|

Biogenesis of Type V pili

Abstract: Pili or fimbriae, which are filamentous structures present on the surface of bacteria, were purified from a periodontal pathogen, Porphyromonas gingivalis, in 1980s. The protein component of pili (stalk pilin), which is its major component, was named FimA; it has a molecular weight of approximately 41 kDa. Because the molecular weight of the pilin from P. gingivalis is twice that of pilins from other bacterial pili, the P. gingivalis Fim pili were suggested to be formed via a novel mechanism. In earlier studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 134 publications
(245 reference statements)
1
22
0
Order By: Relevance
“…The presence of the lipoprotein signal suggests that the string of POTRA domains curl back around to the OM (Figure 1). The same P. gingivalis Bam and Tam proteins were also recently predicted by others (Shoji et al., 2020).…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…The presence of the lipoprotein signal suggests that the string of POTRA domains curl back around to the OM (Figure 1). The same P. gingivalis Bam and Tam proteins were also recently predicted by others (Shoji et al., 2020).…”
Section: Resultssupporting
confidence: 76%
“…A new type of pilus was recently characterized in P. gingivalis and related species. The type V pilins are produced as lipoproteins and polymerized on the cell surface through proteolytic cleavage of the lipidated N‐terminal region and donor‐strand exchange (Shibata et al., 2020; Shoji et al., 2020; Xu et al., 2016). Three pili have been identified, the major (longer) pili (or fimbriae) composed of Fim subunits, the minor pili composed of Mfa subunits and PG1881 (Nagano et al., 2017), which is yet to be fully characterized (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…The FimA and Mfa1 proteins polymerize to form a filamentous structure by a similar mechanism [22]; via proteolytic processing by a signal peptidase and gingipain to yield the mature forms. Then, the C-terminal donor strands of the incoming monomer extend and bind to the hydrophobic groove of the prior monomer [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Then, the C-terminal donor strands of the incoming monomer extend and bind to the hydrophobic groove of the prior monomer [23,24]. This is known as the donor-strand exchange mechanism in the assembly of Escherichia coli fimbriae [25], but unlike in P. gingivalis, chaperone and usher proteins are absent, whereas digestion with protease (gingipain) is involved in maturation [22]. This proteinase-mediated donor-strand exchange mechanism, currently seen only in the class Bacteroidia, is called type V fimbriae [23].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, P. gingivalis possesses a unique class of fimbria subunits [ [9] , [10] , [11] ]. Recent structural analyses and mechanistic studies of the fimbrial proteins of P. gingivalis [ [23] , [24] , [25] ] indicated that P. gingivalis fimbriae were formed by a proteinase-mediated donor-strand exchange mechanism, which were classified as a novel type of fimbriae and designated as Type V fimbriae [ 23 , [26] , [27] , [28] ]. Structurally homologous fimbrial proteins are detected only in the Bacteroidia class [ 23 ], which are integral parts of the human microbiome and are associated with human health and disease.…”
Section: Introductionmentioning
confidence: 99%